The Effect of Long-Term or Repeated Use of Antibiotics in Children and Adolescents on Cognitive Impairment in Middle-Aged and Older Person(s) Adults: A Cohort Study - Liu, Zhou; Wei, Shouchao; Chen, Xiaoxia; Liu, Lingying; Wei, Zhuangsheng; Liao, Zhimin; Wu, Jiayuan; Li, Zhichao; Zhou, Haihong; Wang, Duolao (Frontiers in Aging Neuroscience, 2022)
Objectives: We evaluated the effects of long-term/recurrent use of antibiotics in childhood on developing cognitive impairment in middle and old age from UK Biobank Database. Methods: UK Biobank recruited participants aged 37-73 years. Cognitive impairment was ascertained by fluid intelligence (FI) questionnaire. Primary outcome was the occurrence of cognitive impairment in middle and old age. Multivariate logistic regression models were used to explore the relationship between long-term/recurrent use of antibiotics and cognitive impairment. Results: Over 3.8-10.8 years’ follow-up, 4781 of the 35921 participants developed cognitive impairment. The odds of cognitive impairment in middle and old age among long-term/recurrent use of antibiotics in childhood were increased by 18% compared with their counterparts (adjusted odd ratio [OR] 1.18, 95% confidence interval [CI] 1.08-1.29, p<0.01). The effect of long-term/recurrent use of antibiotics in childhood on cognitive impairment was homogeneous across different categories of various subgroup variables such as sex, age, APOE4, ethnic groups, income before tax, smoking status, alcohol status, BMI, hypertension and diabetes but the effect of long-term/recurrent use of antibiotics in childhood was modified by the educational qualification (p value for interaction < 0.05). Conclusions: Long-term/recurrent use of antibiotics in childhood may increase the risk of cognitive impairment in middle and old age.